Distribution and pollution assessment of heavy metal(loid)s in seawater and organisms in Rongcheng coastal area, China - Yue, Nana; Dong, Chao; Yang, Jiaojiao; Wang, Jianqiang; Feng, Jing; Sun, Jing (Frontiers in Marine Science, 2025)
Marine ecosystems in coastal regions are increasingly threatened by anthropogenic inputs of heavy metal(loid)s, with significant implications for environmental health. This study evaluates the spatial characteristics and ecological risks of heavy metal(loid)s in the Rongcheng nearshore environment through comprehensive analysis of surface water samples and marine organisms collected during summer 2017. Analytical data revealed that seawater concentrations for most measured elements complied with Class I standards (GB 3097-1997), with lead being the sole exception showing moderate contamination at specific sampling locations. Ecological risk assessment through integrated indices demonstrated generally favorable conditions, with both water quality parameters and potential ecological risk values falling within acceptable ranges. Source apportionment analysis differentiated the heavy metal(loid)s into two distinct groups: Cu, Pb, Zn, Cr and As predominantly originating from human activities, whereas Hg and Cd derived mainly from geological processes. Notably, despite typically low aqueous-phase concentrations, these elements demonstrate significant biomagnification potential through trophic transfer processes. Tissue analysis of marine organisms showed compliance with biological quality standards for most elements, except for localized exceedances of Cu and As. Bioaccumulation factors consistently above unity across multiple species highlight considerable seawater-to-organism transfer efficiency. These findings underscore the importance of maintaining seawater quality standards to mitigate potential impacts on marine food webs and human seafood consumption.